PORTABLE MANNEQUIN-BASED AIR POLLUTION EXPOSURE SIMULATOR FOR MASK FILTRATION TEST - Adrian, Martin
Air pollution is one of the impacts of technological and industrial developments. One type of gaseous pollutant, namely particulate matter (PM), can cause respiratory diseases in humans. PM detection can be done using sensors based on light scattering. The development of sensor technology allows the fabrication of sensors with smaller size. PM sensors have now been developed with a relatively smaller size that allows them to be used for portable measurement applications. This research focuses on developing a mask testing instrument using a mannequin simulator. The PM sensor is used to measure and compare the level of pollution received when someone wears a mask and does not wear a mask. The testing equipment is designed so that it can collect data outdoors on motorbikes to describe the pollution exposure to a motorist. The masks tested included N95, cloth masks, and KN95 masks by also paying attention to how the gaps formed between the mask and the face. Testing is done statically and mobile. Static testing in the room shows that the filtration of N95 masks and cloth masks can filter PM up to 80%. The installation of the mask and the design of the mask also have an influence on the gaps that are formed. Mobile testing was carried out to review how masks perform when used outdoors while travelling. The results of the mobile test are almost the same as the static test with the highest filtration order, namely N95, KN95, and cloth masks. Direct mobile measurements can show locations with higher PM levels. The filtration value obtained from the mannequin test can be compared with standard measurements so that an effective filtration value is obtained. Effective filtration describes how much of the ideal filtration value of a mask when used in everyday life.